Case Report: Pathologic complete response to PRaG therapy in an elderly patient with refractory metastatic gastric cancer - Lv, Jun; Yu, Fayi; Pan, Linjiang; Fang, Yeying; Zhong, Zhenghong; Bai, Xue; Gao, Jinbiao; Wei, Zhuxin (Frontiers in Oncology, 2026)
Hepatoid adenocarcinoma of the stomach (HAS) is a rare histologic subtype of gastric cancer with distinct pathological features and poor prognosis. Surgery and chemotherapy remain the primary treatment modalities, but outcomes are generally unsatisfactory. Radiotherapy can enhance tumor immunogenicity by releasing tumor antigens, thereby promoting antitumor immune responses and potentiating the efficacy of immune checkpoint inhibitors. We report a case of advanced HAS that progressed after first-line treatment with chemotherapy, immunotherapy, and targeted therapy. The patient subsequently received a combination of radiotherapy, programmed cell death protein 1 (PD-1) blockade, and granulocyte-macrophage colony-stimulating factor (GM-CSF)—termed PRaG therapy. The tumor demonstrated significant shrinkage following PRaG treatment and ultimately achieved pathologic complete response (pCR), with no serious adverse events aside from mild abdominal pain (NRS score 2). This case suggests that PRaG therapy may represent a promising therapeutic approach for patients with metastatic HAS.